Cleft Lip and Palate Repair Using a Surgical Microscope - Kato, Motoi (Arch Plast Surg, 2017)
BACKGROUND: Cleft lip and palate repair requires a deep and small surgical field and is usually performed by surgeons wearing surgical loupes. Surgeons with loupes can obtain a wider surgical view, although headlights are required for the deepest procedures. Surgical microscopes offer comfort and a clear and magnification-adjustable surgical site that can be shared with the whole team, including observers, and easily recorded to further the education of junior surgeons. Magnification adjustments are convenient for precise procedures such as muscle dissection of the soft palate. METHODS: We performed a comparative investigation of 18 cleft operations that utilized either surgical loupes or microscopy. Paper-based questionnaires were completed by staff nurses to evaluate what went well and what could be improved in each procedure. The operating time, complication rate, and scores of the questionnaire responses were statistically analyzed. RESULTS: The operating time when microscopy was used was not significantly longer than when surgical loupes were utilized. The surgical field was clearly shared with surgical assistants, nurses, anesthesiologists, and students via microscope-linked monitors. Passing surgical equipment was easier when sharing the surgical view, and preoperative microscope preparation did not interfere with the duties of the staff nurses. CONCLUSIONS: Surgical microscopy was demonstrated to be useful during cleft operations.